A, The Penerapan Pendekatan Penyelesaian Soal Secara Sistematis (PSSS) Untuk Meningkatkan Hasil Belajar Siswa Dalam Pembelajaran Pendidikan Agama Hindu dan Budi Pekerti Pada Siswa Kelas VIII.7 Di SMP Negeri 7 Denpasar: Penerapan Pendekatan Penyelesaian Soal Secara Sistematis (PSSS) dan Peningkatan Hasil Belajar Siswa - Meira Yanti, Putu; Yasa, I Made Wiguna; Dewi, Ni Wayan Sri Prabawati Kusuma (UHN IGB Sugriwa Denpasar, 2025)
This research was motivated by problems with student learning outcomes and student learning activities. In this learning, students are less active in the learning process of Hindu Religious Education and Character. The reason why there are still many students who are less active in learning Hindu Religious Education and Character and get less grades than the KKTP is that teachers still use the lecture method in delivering learning material. The problems that will be discussed include (1) The learning activities of class VIII.7 students in the second semester of the 2023/2024 academic year in Hindu religious education whose learning process uses a systematic problem solving approach (PSSS) assisted by LKS (2 Applying the Question Solving Approach It will systematically improve the learning outcomes of class VIII.7 students in the second semester of the 2023/2024 academic yearThis research aims to find out (1) To find out whether the implementation of Systematic Problem Solving can improve the learning outcomes of Hindu Religious Education class VIII.7 at SMP Negeri 7 Denpasar in the 2023/2024 Academic Year. (2) To find out whether the application of systematic problem solving can improve the learning outcomes of Hindu Religious Education for class VIII.7 students at SMP Negeri 7 Denpasar in the 2023/2024 academic year. The results of the research show (1) It is known that students' learning completeness in the implementation of the pretest in cycle I obtained a total of 2375 scores with an average of 59, the highest score was 70 and the lowest was 40. (2) Meanwhile the learning results in cycle II were 2,900 (pre test score) and 3330 (post test score). (3) It can be concluded from the two cycles that have been implemented, the second cycle has a high learning outcome value compared to the first cycle, so that learning completeness is achieved. Keywords: Student Learning Outcomes, Systematic Problem Solving Approach (PSSS), Learning Completeness